Cancellation and resilience through song: from Carmen Miranda to Karol Conká (PerCursos, 2024)
This study aims to analyze the use of music as a response to the "cancelation" experienced by Carmen Miranda and Karol Conká. Despite the temporal and experiential differences, both faced controversies in their careers and turned to song as a means to express their perspectives. The study seeks to examine the meaning of these songs, contributing to the debate on "cancelation" in contemporary culture. The work is divided into three parts: introduction, presentation of the context of "cancelations", and analysis of the songs, aiming to deepen our understanding of the impact of "cancelation" on artists' lives and alternatives to confront it. After analyzing the two songs, "Disseram que voltei americanizada" revealed Carmen Miranda reaffirming her Brazilian identity, while in "Paredawn," Karol Conká reflects on her cancelation while simultaneously criticizing the behavior of the "canceling" mass.
Keywords: popular song; Carmen Miranda; Karol Conká; cancel culture; mass theory